Miranda era essas pedras”: Estado, mineração e conflitos em uma comunidade quilombola - Cascaes, Barbara de Sousa (2017)
Miranda do Rosário is located at Rosario, Maranhão, 70 km from the capital of the state, São Luís. Large projects encouraged by the State establish different conflict situations in the region of the Eastern Amazon, the Rosario region an area of interest to development politics. The announcement of the arrival of Petrobras“ Premium I Refinery at Bacabeira has brought forth impacts in several aspects of neighboring municipalities, including Rosario, reaching a diversity of traditional groups and communities with increased real estate speculation, threats of compulsory displacement and environmental damage. People of Miranda bring in their narratives about the city the various conflicts that the community has experienced since the l970s, a period of increase of government agencies in order to growth of agricultural projects in the Eastern Amazon, making it difficult for the group to access natural resources as a hedge of Babaçu until then freely available. In the following decades the conflicts changed configuration with the progression of mining companies involved with the exploitation of rocks for the civil construction causing great environmental damages and threats of expulsion. The mobilization of the community to face the threats enabled the group to be recognized as a remaining “quilombo” community receiving the certification of the Palmares Cultural Foundation in the year of 2010. This work is aimed to describe several situations of conflicts throughout the history of the group from the voices of the social agents themselves and to examine social conditions that allow the presence of different antagonists and the relations established in the exploitation of the ecological resources guaranteed by the State.